Toxicity study on marine organisms due to drilling fluids - Ismail, Abdul Razak; Ahmad, Noor Jana; Anam, Muhd. Noorul (Faculty of Chemical & Natural Resources Engineering, UTM Skudai, 1997)
Drilling fluids or usually know as drilling muds must be used to drill or gas wells. Two types of muds that are normally used in drilling operation are water based muds and oil based muds (diesel and mineral oil). Drilling muds are complex mixtures which contain many types of additives and chemicals which may pollute the environment if necessary precautions are ignored. Because of this effect, many countries have introduced certain regulation to control this problem. Studies have been conducted to evaluate the toxicity effects of the three drilling fluid systems to marine life. The toxicity tests were carried out using local marine species namely tiger prawn (Penaeus Monodon) for the suspended particle phase of the drilling fluid systems and cockle (Anadara Granosa L.) for the solid phase of the drilling fluid systems. Results show that the oil based mud (diesel) caused the highest mortality of tiger prawn during the 96 hours of the toxicy test. The results also suggest that the lower concentration of suspended particle phase from the oil based mud (diesel) can kill 50% of tiger prawn in the range of 300 ppm compared to the oil based mud (mineral oil) which is in range of 600 to 700 ppm and water based (5000 to 6000 ppm). However, for the solid particle test, water based mud shows higher toxicity compared to the ok based muds (diesel and mineral oil). Ten days exposure of cockle to the solid phase sample shows that water based mud indicates the highest mortality (87%) compared to the oil based mud (diesel) which is 73% and oil based mud (mineral oil) which is 53%. These results suggest that drilling fluid systems should be carefully formulated to minimize the effect of pollution to the environment.